Validation of the Patient Health Questionnaire-2 with Iranian students. Issue 10 (26th November 2019) - Dadfar, Mahboubeh; Salabifard, Sedigheh; Dadfar, Tayebeh; Roudbari, Masoud; Moneni Safarabad, Nahid
ABSTRACT: Depression is a serious public health problem in community settings and primary care. The Patient Health Questionnaire-2 (PHQ-2) is a brief screen for depression. The PHQ-2 has not had its validity examined in academic settings in Iran. A cross-sectional study was conducted to investigate the reliability, validity, and factorial structure of the PHQ-2 in a convenience sample of 157 Iranian volunteer college students selected from the Iran University of Medical Sciences. Participants completed the PHQ-2, and the Loneliness Scale (LS). The mean score of the PHQ-2 was 2.26 ( SD = 1.64). The Cronbach's α coefficient was .74, indicating high internal consistency. The PHQ-2 correlated .68 with the LS, demonstrating good construct validity. The results of the factor analysis of the PHQ-2 identified one factor labeled: General depression (79.87% of the variance). The PHQ-2 has a unidimensional structure, acceptable validity and reliability, and it can be used in the non-clinical settings in Iran.